An Analysis of Indonesian Administration of Criminal Legislation as Instrument of Restorative Justice for Prisoners - Uche Nnawulezi; Jacques Kabano; Fadhel Arjuna Adinda; Dorcas Adesola Thanni; Mary-Ann Onoshoke Ajayi (Indonesian Journal of Criminal Law Studies, 2025)
This paper seeks to examine the extent to which restorative justice principles have been integrated into Indonesia's criminal justice process, particularly concerning sentenced offenders. However, in Indonesia, while criminal enforcement concerning the rights of suspects and accused individuals are provided in several legislations, the aspects of victims’ protection have remained unattended to. The paper therefore argued for the review of the administration of criminal justice legislations and retraining of officials under the criminal justice system in order to strengthen the justice system and her service delivery. While these reforms are widely regarded as an essential task’s, the paper explores the challenges encountered in implementing restorative justice for Indonesian Prisoners, especially at the investigation stage. The paper’s analysis revealed how law enforcement agencies, like the Indonesian National Police, can practically apply restorative justice principles to create more robust frameworks for its use. Drawing on the analysis of the paper, it argues that despite efforts made to promotes restorative justice, differences still exists between traditional criminal concepts and its applications in Indonesia. Examining the findings of the paper, it concludes that there is need to align investigative methods with restorative justice principles in order to be able to address minor offences effectively and improve community well-being.